2017
DOI: 10.1007/s10792-017-0677-1
|View full text |Cite
|
Sign up to set email alerts
|

The association of Helicobacter pylori with choroidal and retinal nerve fiber layer thickness

Abstract: CT increases during H. pylori infection and returns to the normal range within 6 weeks of treatment. RNFLT does not show any change during H. pylori infection. The data related to the subfoveal CT may be useful in understanding the pathogenesis of central serous chorioretinopathy developing in H. pylori patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…In another study by Horozoglu et al, it was observed that there was no increase in choroidal thickness values in H. pylori positive patients without CSCR ( 38 ). Can et al reported that choroidal thickness values were found to be increased in adult patients with H. pylori infection and regression of choroidal thickness with treatment was shown ( 39 ). Contrary to the controversial results in the studies conducted in the adult age group, we think that the main factor in the formation of the statistical difference arises from the fact that aging and decreasing vascular elasticity and compliance.…”
Section: Discussionmentioning
confidence: 99%
“…In another study by Horozoglu et al, it was observed that there was no increase in choroidal thickness values in H. pylori positive patients without CSCR ( 38 ). Can et al reported that choroidal thickness values were found to be increased in adult patients with H. pylori infection and regression of choroidal thickness with treatment was shown ( 39 ). Contrary to the controversial results in the studies conducted in the adult age group, we think that the main factor in the formation of the statistical difference arises from the fact that aging and decreasing vascular elasticity and compliance.…”
Section: Discussionmentioning
confidence: 99%
“…As a metabolically active tissue, the retina consumes many nutrients and oxygen [11] . Among the body's blood vessels, the choroid has the highest blood flow per unit of tissue weight, which is responsible for supplying oxygen and nutrients to the retina [12][13] . Physiological conditions and systemic disorders can affect the retina or choroid [14][15] .…”
Section: Introductionmentioning
confidence: 99%